PENDAMPINGAN PELATIHAN ALAT MUSIK ANGKLUNG BAGI ANAK USIA SEKOLAH DASAR MENGGUNAKAN METODE HAND SIGN KODALY DI DESA PASIR JAYA, KECAMATAN CIGOMBONG, KABUPATEN BOGOR (Universitas Esa Unggul, 2022)
Angklung music which has been introduced to elementary school age children in Pasir Jaya Village, during the Covid 19 pandemic in 2020 has had a very big impact on these children. The children become happy, excited and consistently learn and practice music with the angklung musical instrument. Some elementary school age children in Pasir Jaya Village are finally adept at playing angklung music with songs from the Sundanese region, especially the Manuk Dadali song. So that the ability to play the angklung musical instrument with Sundanese folk songs as cultural roots in Pasir Jaya Village does not fade, and this game can have a greater impact on these children, then in this community service in 2021, the development of the angklung musical instrument is carried out. while preserving Sundanese culture. In accordance with this goal, training on angklung musical instruments with Sundanese songs is given, which is led by a conductor who uses sign language to direct the notes, replacing song notes written on paper or boards, known as the Kodaly hand sign method. The benefits of the Kodaly hand sign method are besides being more practical, it makes children accustomed and trained to memorize. So that in turn these habits can make children smarter in receiving lessons at school. On the other hand, it can also be used to perform on a wider stage, not limited to children in their home environment. The end result of the dedication that has been achieved is, the children are accustomed to playing angklung music with Sundanese songs, returning to appreciate Sundanese culture, getting used to playing angklung led by the conductor using the Kodaly hand sign method, and performing angklung music with outsiders, namely front students in the city of Bogor and its surroundings. Keyword: Sunda Heritage, Angklung, hand sign kodaly